Prevalence of depression and suicidal ideation in trauma patients in western Rajasthan (Panacea Journal of Medical Sciences, 2022)
Background: Depression is a common psychiatric disorder in trauma patients. Early detection of depression in a traumatized patients can help alleviate long-term symptoms and adverse effects associated with depression. This study aimed to determine the prevalence of depression and suicidal ideation in trauma patients after one month of injury.Materials and Methods: Hospital-based cross-sectional study was carried out among 120 individuals with a history of trauma from March 2020 to May 2020. Purposive sampling was used to recruit participants over a specified period. The Beck's Depression Inventory-II (BDI-II) was used to measure depression intensity and suicidal ideation. The statistical analysis was carried out using SPSS version 20.Results: The study included a total of 120 participants. The prevalence of depression was 30% in study participants. In our study, 8 (44.44%) of 18 participants over the age of 60, 30 (36.59%) of 82 male participants, 9 (64.29%) of 14 separated or divorced participants, 17 (45.95%) of 37 illiterate participants, 25 (43.86%) of 57 participants from low socioeconomic backgrounds, and 23 (42.59%) of 54 participants from rural backgrounds had more depression. Twenty (46.51%) out of 43 polytrauma participants, 5 (45.45%) out of 11 participants injured due to violence, 31 (33.70%) out of 92 participants who had a history of more than 48 hrs hospitalization, and 17 (48.57%) out of 35 participants had a history of ICU admission had more depression. Twenty-one participants (58.33%) of the 36 who suffered from depression had suicidal thoughts or intentions.Conclusion: Suicidal ideation and depression were more common in traumatic patients. Physicians' treatment should not be limited to early physical rehabilitation. They must also prioritise early mental rehabilitation in order to avoid long-term issues with mental and physical disabilities.